Effect of an isoenergetic traditional Mediterranean diet on apolipoprotein A-I kinetic in men with metabolic syndrome. - Richard, Caroline.; Couture, Patrick.; Desroches, Sophie.; Lichtenstein, Alice H.; Lamarche, Benoît. (2016)
Background: The impact of the Mediterranean diet (MedDiet) on high-density lipoprotein (HDL) kinetics has not been studied to date. The objective of this study was therefore to investigate the effect of the MedDiet in the absence of changes in body weight on apolipoprotein (apo) A-I kinetic in men with metabolic syndrome (MetS).; Keywords: Diet, Apolipoproteins, Lipoproteins, Obesity, Metabolism.; Springer Open.